Surgical intervention as a curative major for secondary hypertension - Tambat, Ramesh Mahadev; Narasimhaiah, Venuprasad; Collin, Marshall David; Sannappanavar, Nataraj Y.; Kumar, Nitin; Shrestha, Yogendra; Moktan, Jeet Bahadur (International Surgery Journal, 2021)
Retroperitoneal functional paraganglioma is a rare type of neuroendocrine neoplasm which secrete excess catecholamines including epinephrine, norepinephrine, dopamine and their metabolites metanephrine, normetanephrine, 3-methoxytyramine respectively. Early diagnosis of functional paraganglioma is important because its removal is often curative. The extent of disease is evaluate using 2(18F)-fluoro-2 deoxy-D-glucose positron emission tomography (FDG-PET), where increased uptake of 18-FDG observed the mass. It is one of the rare curable causes of secondary hypertension. Here, we have presented the rare case of a young female who was recently diagnosed with hypertension and pain in abdomen, was later found to have functional paraganglioma.